Strategic marketing cases in emerging markets - Adhikari, Atanu; Roy, Sanjit Kumar (Springer, 2017)
This book helps students to develop a critical understanding of the service business scenarios and strategies used in marketing for emerging markets. The case studies presented focus on creating, communicating and delivering customer value to emerging market consumers through various marketing strategies, processes and programs in the context of emerging market dynamics, consumer diversity, and competitors. By illustrating a range of actual business situations, this case book will help students acquire the skills they need to make informed marketing decisions in emerging markets. Further, it provides instructors, students, and practitioners alike a framework for understanding the strategic marketing dynamics at work in these countries. Strategic Marketing Cases in Emerging Markets is a timely work which I believe has successfully addressed the long-standing need for a suitable case book capturing diverse Strategic Marketing issues in transitional economies. These issues are currently generating a great deal of interest amongst marketing students, academics and practitioners, who I am sure will find this book useful. Professor Ali Quazi, University of Canberra, Australia Anyone interested in the challenges of global marketing will find this book of immense interest and value. It offers case studies from a range of countries and industry sectors which together provide an excellent insight into how to ensure that marketing strategies are effective in emerging markets. Professor James Devlin, University of Nottingham, UK Sanjit and Atanu have compiled a very concise but broad collection of case studies that will be extremely relevant for academics and researchers who focus on emerging markets. Professor G. Shainesh, Indian Institute of Management, Bangalore, India This is a fascinating set of insights, for students and practitioners alike. Timely pointers and suggestions for best practice emerge throughout this smartly selected set of cases. Well worth dipping into or adopting for courses exploring international marketing, marketing strategy, consumer behaviour or strategic management. Professor Lyndon Simkin, Coventry University, UK.
Keywords: Marketing -- Management -- Case studies.; Globalization.; Markets.; elektronické knihy; electronic books